INVENTORY OF SPARE PARTS FOR AUTOMOBILE PULL DEPDIKNAS ON USING MICROSOFT VISUAL BASIC 6.0 - Endriyono Endriyono; Syahril, SKom Syahril, SKom (Jurnal Sistem Informasi, 2006)
Recording inventory of spare parts using computer assistance can facilitateinformed that there are spare parts inventory in the warehouse Pull Ministry,because stocks of spare parts directly in the update every time there was atransaction.Purchases can be made easier oversight, because if the spare parts to be purchasedexceeds the limit of spare parts inventory in the warehouse, users can learnquickly.